DESIGN AND SIMULATION OF A GUIDANCE AND CONTROL SYSTEM FOR GLIDING MUNITIONS - Alaçam, Muhammed; Çiçek, Osman (Dicle Universitesi Muhendislik Fakultesi Muhendislik Dergisi, 2024)
In this paper, a fixed wing, tail fin controlled gliding munition has been designed. A guidance and control system is developed for the designed model and the glide towards the target is tested in the XPLANE 11 flight simulator environment. The simulation was carried out in two stages, both in the software loop and in the hardware loop. After the munition system is released from the aircraft, it measures the angles that will enable gliding to the target coordinates with the guidance system and starts to control fin movements. It compares the instantaneous position data received from GPS with the target position data. With the LOS method, the pitch angle is found by comparing the heading angle required to reach the target and the instantaneous altitude information with the target altitude information. The angles found are compared with the information from the IMU sensor and the errors are processed in the PID controller. The output of the PID controller is converted as a PWM signal to the tail fins in accordance with the munition dynamics. The system was transferred to XPLANE 11 and scenarios with different initial conditions were tested.